Consideration of the role of protein quality in determining dietary protein recommendations - Wolfe, Robert R.; Church, David D.; Ferrando, Arny A.; Moughan, Paul J. (Frontiers in Nutrition, 2024)
The quality of a dietary protein refers to its ability to provide the EAAs necessary to meet dietary requirements. There are 9 dietary amino acids that cannot be metabolically produced in the body and therefore must be consumed as part of the diet to avoid adverse metabolic consequences. These essential amino acids (EAAs) serve a variety of roles in the body. The amount and profile of the dietary EAAs relative to the individual EAA requirements and the digestibility of the dietary protein are the key factors that determine its quality. Currently the Digestible Indispensable Amino Acid Score (DIAAS) is the best available approach to quantifying protein quality. The most prominent metabolic role of dietary EAAs is to stimulate protein synthesis by serving as signals to activate molecular mechanisms responsible for the initiation of protein synthesis and, most importantly, to provide the necessary precursors for the synthesis of complete proteins. Current dietary recommendations generally do not consider protein quality. Accounting for protein quality in dietary patterns can be accomplished while staying within established ranges for dietary protein consumption. Poor protein quality can be compensated for to some extent by eating more low-quality protein, but to be effective ("complementary") the limiting EAA must differ between the low-quality protein and the base diet to which it Is being supplemented. Adding a high-quality protein to a dietary pattern based on low-quality protein is more effective in meeting EAA goals than increasing the amount of low-quality protein, even if the low-quality proteins are complementary. Further, reliance entirely on low-quality protein food sources, particularly in circumstances that may benefit from a level of dietary EAAs greater than minimal requirements, is likely to include excessive caloric consumption. Protein consumption in high-income nations is generally perceived to be adequate or even excessive, assessment of dietary patterns indicates that a significant percentage of individuals may fall short of meeting optimal EAA intake, especially in circumstances such as aging in which the optimal EAA consumption is greater than basal values for healthy young individuals. The case is made that protein quality is an important consideration in meeting EAA requirements.